2020
DOI: 10.1242/dev.181545
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 regulates developmental lymphangiogenesis by upregulating CXCR4 in the mouse-tail dermis

Abstract: Lymphangiogenesis plays important roles in normal fetal development and postnatal growth. However, its molecular regulation remains unclear. Here, we have examined the function of forkhead box protein O1 (FOXO1) transcription factor, a known angiogenic factor, in developmental dermal lymphangiogenesis using endothelial cell-specific FOXO1-deficient mice. FOXO1deficient mice showed disconnected and dilated lymphatic vessels accompanied with increased proliferation and decreased apoptosis in the lymphatic capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…A recent study reported that viral ectopic expression of FOXO1 in ductal pancreatic adenocarcinoma cells upregulates LINC01197 (LETR1), resulting in the inhibition of cell proliferation 85 . Interestingly, FOXO1 has previously been shown to promote LEC migration and to participate in the regulation of lymphatic development 86,87 . Moreover, in our sequencing data, FOXO1 was significantly more highly expressed in LECs than BECs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that viral ectopic expression of FOXO1 in ductal pancreatic adenocarcinoma cells upregulates LINC01197 (LETR1), resulting in the inhibition of cell proliferation 85 . Interestingly, FOXO1 has previously been shown to promote LEC migration and to participate in the regulation of lymphatic development 86,87 . Moreover, in our sequencing data, FOXO1 was significantly more highly expressed in LECs than BECs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FoxO protein is inactivated by major carcinogenic signals such as phosphatidylinositol-3 kinase pathway and MAP kinase . FoxOs regulate the expression of many genes to control many cell functions, such as cell growth (Niimi et al, 2019), survival (Hassell, 2019), metabolism and antioxidant status (ZeÄŤić & Braeckman, 2020). However, recent studies have shown new and unknown functions of FoxO in cancer treatment and promotion, which shows that FOXO factor, has complex roles in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FOXO1 has previously been shown to promote LEC migration and to participate in the regulation of lymphatic development 76,77 . Moreover, in our sequencing data, FOXO1 was significantly more highly expressed in LECs than BECs.…”
Section: Discussionmentioning
confidence: 99%